Nurse Hand Hygiene Behavior with Prevention of Surgical Site Infection In Surgery Room - Candra Intan (Journal of Applied Nursing and Health, 2021)
Background: The Surgical Site Infection (SSI) is caused by several factors including surgery, invasive measures, equipment and use of antibiotics. The SSI is an infection problem that occurs in patients during the treatment process in hospitals or other health facilities. These infections that are obtained at the hospital both occur in patients when receiving care, health workers who work in hospitals and visitors to hospitals. The purpose of this research is to find out the relationship between Nurses Behavior and Prevention of in the Mokoyurli Hospital Surgery Room, Buol Regency.Methods: The design used in the study is crossectional analytic. The population is All Nurses in the Surgery Room. The sample size was 19 respondents using the Total Sampling technique. Independent variable of research is the behavior of hand washing. The dependent variable is prevention of infection. Data was collected using observation sheets, then the data were analyzed using the Chi-Square test with a significance level of α ≤ 0.05.Results: The results showed that more than half of the respondents had good hand washing behavior as many as 10 respondents (52.6), Enough as many as 7 respondents (36.8%), Less as many as 2 respondents (10.5%). Non-infectious events were 14 respondents (73.3%), and the incidence of infection was 5 respondents (26.3%). The results of statistical tests obtained p = 0.023 with <0.05, which means that there is a significant relationship to the variable handwashing behavior with infection.Conclusion: Washing hands during the implementation of nursing actions is the most effective way to prevent the occurrence of the Surgical Site Infection in the hospital environment.